2018
DOI: 10.1007/s00268-018-4599-5
|View full text |Cite
|
Sign up to set email alerts
|

Time Attributable to Obesity in Surgery: A Multi‐specialty Report on Day‐of‐Surgery Resource Utilization from 189,264 Cases

Abstract: Our study quantified day-of-surgery resource utilization for 14 major surgical procedures by BMI category. The need for additional resources to accommodate patients in higher BMI groups was consistent across all procedures studied and was primarily reflected by lengthened operative times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In contrast, many prior investigations into resource utilization have been specialty- or procedure-specific investigations. 26 , 27 , 28 Our integrated approach highlights how perioperative decision-making can be integrated into a hospital’s ultimate responsibility to public health in a time of critical shortages of resources due to community infectious risks.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, many prior investigations into resource utilization have been specialty- or procedure-specific investigations. 26 , 27 , 28 Our integrated approach highlights how perioperative decision-making can be integrated into a hospital’s ultimate responsibility to public health in a time of critical shortages of resources due to community infectious risks.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although obesity has been shown to effect surgical time across all common major surgeries, a 2019 study of 469 thyroidectomy patients found no significant difference in operative time between obese (body mass index 30 kg/m 2 ) and nonobese patients. 18,19 Based on this information it is reasonable to conclude that it would be possible for individual surgeons to accurately predict their operative time.…”
Section: Introductionmentioning
confidence: 98%